Progress in hydroxyapatite-starch based sustainable biomaterials for biomedical bone substitution applications - Miculescu, Florin; Maidaniuc, Andreea; Voicu, Stefan Ioan; Kumar Thakur, Vijay; Stan, G. E.; Ciocan, L. T. (American Chemical Society, 2017)
Hydroxyapatite is a calcium phosphate intensively proposed as a bone substitution material because of its resemblance to the constituents of minerals present in natural bone. Since hydroxyapatite’s properties are mainly adequate for nonload bearing applications, different solutions are being tested for improving these properties and upgrading them near the target values of natural bone. On the other hand, starch (a natural and biodegradable polymer) and its blends with other polymers have been proposed as constituents in hydroxyapatite mixtures due to the adhesive, gelling, and swelling abilities of starch particles, useful in preparing well dispersed suspensions and consolidated ceramic bodies. This article presents the perspectives of incorporating starch and starch blends in hydroxyapatite materials. Based on the role of starch within the materials, the review covers its use as (i) a polymeric matrix in hydroxyapatite composites used as adhesives, bone cements, bone waxes, drug delivery devices or scaffolds and (ii) a sacrificial binder for fabrication of porous hydroxyapatite scaffolds. The suitability of these materials for bone reconstruction has becomes a reachable aim considering the recent advancements in ceramic fabrication and the current possibilities of controlling the processing parameters.
Keywords: Hydroxyapatite; Starch; Gelatin; Chitosan; Silk fibroin; Cellulose acetate; Starch blends; Starch composites; Porous ceramics; Scaffolds; Drug-delivery systems; Bone cements